Aldosterone in Gynecology and Its Involvement on the Risk of Hypertension in Pregnancy - Sabbadin, Chiara; Andrisani, Alessandra; Ambrosini, Guido; Bordin, Luciana; Donà, Gabriella; Manso, Jacopo; Ceccato, Filippo; Scaroni, Carla; Armanini, Decio (Frontiers in Endocrinology, 2019)
Aldosterone is the main mineralocorticoid hormone, responsible of the regulation of fluid and electrolyte balance and blood pressure. It acts also as a pro-inflammatory factor responsible of an increased cardiovascular risk, independent from blood pressure values. After the discovery of mineralocorticoid receptor (MR) in mononuclear leukocytes, further studies support its role in inflammatory and even autoimmune mechanisms underlying several diseases. In particular, recent studies reported a possible involvement of aldosterone in some gynecological conditions and diseases, characterized by inflammation, hypertension and increased cardio-metabolic risk, such as use of hormonal contraceptives, preeclampsia, polycystic ovary syndrome, uterine fibroids and endometriosis. The aim of this mini-review is to report the possible involvement of aldosterone in all these gynecological conditions, suggesting different pathogenetic mechanisms and new target treatments of MR blockers for these diseases.